2002
DOI: 10.1590/s0021-75572002000100006
|View full text |Cite
|
Sign up to set email alerts
|

Meningite pneumocócica na infância: características clínicas, sorotipos mais prevalentes e prognóstico

Abstract: These findings suggest that pneumococcal meningitis presents high mortality and morbidity and that the 7-valent conjugate vaccine would be potentially useful in preventing serious pneumococcal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
19

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 15 publications
4
13
0
19
Order By: Relevance
“…8,4,[10][11][12] Of this study, seven (54%) of the 13 children less than 2 years old had suffered IPD due to SpNSPn. It is possible that this high level of penicillin resistance is partially due to the fact that HIV+ patients are often given antimicrobial treatment.…”
Section: %mentioning
confidence: 72%
See 2 more Smart Citations
“…8,4,[10][11][12] Of this study, seven (54%) of the 13 children less than 2 years old had suffered IPD due to SpNSPn. It is possible that this high level of penicillin resistance is partially due to the fact that HIV+ patients are often given antimicrobial treatment.…”
Section: %mentioning
confidence: 72%
“…The majority of these refer to colonization of the airways by Sp, since the difficulties in isolating the bacteria from cultures from people with pneumonia are well known. 4,[9][10][11][12][13] The only study published in Brazil on Sp serotypes identified from HIV+ children demonstrated that nasopharyngeal colonization of 112 children was no greater than that described in the literature for healthy children. 3 In our study, serotype 14 was the most frequent (four cases) and was also the serotype that exhibited greatest resistance to penicillin, which confirms data published in Brazilian literature.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[1][2][3] In spite of pneumonias causing the largest number of deaths, the mucosal diseases caused by pneumococcus are more common, and the use of antibiotics to treat otitis and sinusitis have been associated with the appearance and dissemination of antibiotic resistant strains. [4][5][6][7] Pneumococcal diseases are more common in children younger than 2 years, elderly people, and in certain groups of individuals that present conditions associated with the development of invasive pneumococcal diseases (IPD) ( Table 2). [1][2][3][4][5][6][7][8][9][10][11][12] Moreover, they affect poorer populations more seriously, aggravating the situation of these populations even further.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Pneumococcal diseases are more common in children younger than 2 years, elderly people, and in certain groups of individuals that present conditions associated with the development of invasive pneumococcal diseases (IPD) ( Table 2). [1][2][3][4][5][6][7][8][9][10][11][12] Moreover, they affect poorer populations more seriously, aggravating the situation of these populations even further. 1,4 In Brazil, the highest rate of incidence of pneumococcal meningitis has been registered in nursing infants younger than 1 year, and bacterial resistance has increased progressively.…”
Section: Introductionmentioning
confidence: 99%